Road Transport Infrastructure and Manufacturing Location: An Empirical Evidence and Comparative Study between Tijuana and Nuevo Laredo, Mexico - Saúl OBREGÓN-BIOSCA; José Manuel CHÁVEZ-USLA; Eduardo BETANZO-QUEZADA (El Colegio de la Frontera Norte, A.C., 2014)
Transport infrastructure influences the location of manufacturing firms in that sense, this paper compares the influence of accessibility to ports for export and the location of manu- facturing firms in two municipalities in the northern Mexico border. The tools used include the management of a geographic information system and micro-level data of the industrial parks of each municipality. Statistical analysis was based on the application of Poisson mod- els to estimate the sets placement options. The results show that accessibility and market size have greater significance in the location of firms in both cities.